2005
DOI: 10.1002/ijc.21396
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Epstein‐Barr viral load in serum of individuals from nasopharyngeal carcinoma high‐risk families in Taiwan

Abstract: The utility of EBV load as a tumor marker in nasopharyngeal carcinoma (NPC) patients suggests that it might also serve as a screening test for individuals who are at high risk for developing NPC. We previously demonstrated that unaffected individuals from high-risk families had elevated anti-EBV antibody levels compared to community controls. In this study, we measured EBV load using 2 different real-time PCR assays (targeting BamH1W and polymerase gene sequences, respectively) carried out in 2 independent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 22 publications
6
29
0
Order By: Relevance
“…Consistent with findings from Taiwan, EBV DNA in plasma was detected in similar frequencies of relatives and controls [Yang et al, 2006]. Thus, the presence of EBV in plasma is much less frequent in unaffected individuals at high risk of developing nasopharyngeal carcinoma than in nasopharyngeal carcinoma patients, which implies that the presence of EBV in plasma of nasopharyngeal carcinoma patients is the result of the tumor.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with findings from Taiwan, EBV DNA in plasma was detected in similar frequencies of relatives and controls [Yang et al, 2006]. Thus, the presence of EBV in plasma is much less frequent in unaffected individuals at high risk of developing nasopharyngeal carcinoma than in nasopharyngeal carcinoma patients, which implies that the presence of EBV in plasma of nasopharyngeal carcinoma patients is the result of the tumor.…”
Section: Discussionsupporting
confidence: 86%
“…EBV DNA is detected in plasma in the majority (75-96%) of nasopharyngeal carcinoma patients from nasopharyngeal carcinoma high-incidence regions, and cell-free EBV DNA is used both as a marker for nasopharyngeal carcinoma detection and for monitoring the disease [Lo et al, 2000;Chan and Lo, 2002;Yang et al, 2006]. Consistent with findings from Taiwan, EBV DNA in plasma was detected in similar frequencies of relatives and controls [Yang et al, 2006].…”
Section: Discussionsupporting
confidence: 83%
“…43 But despite promising findings, Yang et al cautioned that the close association between plasma EBV DNA and the tumor might render it undetectable when identifying precursor lesions or early stages of NPC. 44 On the basis of independent studies quantifying plasma EBV DNA of primary NPC cases, 45 we found that some EBV microRNAs are present at comparable, if not higher copies and may be more readily detectable than EBV DNA under screening circumstances. Identifying EBV microRNAs more exclusive to NPC may also aid in screening against other EBV-associated malignancies that demonstrate elevated levels of circulating EBV DNA.…”
Section: Discussionmentioning
confidence: 87%
“…Previous research has reported that cell-free EBV DNA can be quantitatively measured in the blood of NPC patients using polymerase chain reaction (PCR) technique Shotelersuk et al, 2000;Lin et al, 2001;Chan et al, 2003;Fan et al, 2004). Recent studies have demonstrated that the plasma EBV-DNA level might be a sensitive and reliable biomarker for the diagnosis of NPC at a molecular level/ clinical practice (Fan et al, 2004;Shao et al, 2004;Zhang et al, 2004;Yang et al, 2006). Samples which showed positivity for serum DNA were also positive for tissue DNA, which suggests that the serum EBV DNA originated from NPC and could be use as a marker for tumor DNA.…”
Section: Introductionmentioning
confidence: 99%